The Internal rhythm in the poetry of Sharif Al-Radi and Muhammad Saeed Al-Haboubi: A Critical study - Jassim Al-Majmai, Maryam Muhammad; Asaad, Narges Khalaf; Ahmed, Minas Shihab (Journal of Tikrit University for Humanities, 2023)
This research includes a statement of the "critical balance" between the two selected poets in (inner rhythm), and through which they reveal the points of similarity between them in those poetic texts and judge them according to the monetary provisions. We find that both of them are proficient in the internal rhythm. Repetition in all of its types: repetition of the letter, repetition of the word, and repetition of the phrase or sentence are present in their poetry. This indicates the ability and ingenuity of the poets, as they represent a prominent presence in the linguistic and musical performance of the poets.